Temperature Tests of Varnish-Paint Materials - Sobirov Ma’murjon Marufjonvich (Zien Journals, 2022)
Among the users of cars there is an opinion that the metal does not burn, of course, so there is no need to protect it from fire and heat. This is partly true. Metal structures do not burn at Fire temperature, but they lose their strength significantly. But the varnish on the top of the metal can melt, move, even burn the coatings at high temperature
Keywords: varnish-paint coating; hydrocarbon; cellulose fires; powder